1965
DOI: 10.1080/00288233.1965.10423729
|View full text |Cite
|
Sign up to set email alerts
|

Variability in sexual reproduction of Phytophthora cinnamomi Rands

Abstract: Sixteen New Zealand and 10 overseas isolates of Phytophthora cinnamomi Rands have been compared for oospore production in paired and single cultures. Considerable variability existed among th~ 26 isolates in respect of mating ability and responses to physical and chemical factors. Addition of steroids and related materials did not influence oospore production. However, hypoxanthine increased oospore production in two isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1967
1967
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…The original isolates had been passaged through Granny Smith apples prior to commencing the experiments, but this may not be as reinvigorating as natural infection of a host. There was no association between growth rates and geographic origin of the isolates, which is in line with the findings of Chee and Newhook (1965). Unlike the radial growth on agar, no sporangia production and zoospore release were observed outside temperature range 10-30°C prior to "training."…”
Section: Discussionsupporting
confidence: 85%
“…The original isolates had been passaged through Granny Smith apples prior to commencing the experiments, but this may not be as reinvigorating as natural infection of a host. There was no association between growth rates and geographic origin of the isolates, which is in line with the findings of Chee and Newhook (1965). Unlike the radial growth on agar, no sporangia production and zoospore release were observed outside temperature range 10-30°C prior to "training."…”
Section: Discussionsupporting
confidence: 85%
“…Since then there have been numerous reports on pathogenicity, macro-morphological (colony type * Corresponding author. and growth rate) and micro-morphological (sporangial, gametangial and chlamydospores) variation among worldwide (Galindo & Zentmyer 1964, Zentmyer et al 1976, Zentmyer 1980, national (Haasis, Nelson & Marx 1964, Chee & Newhook 1965, Dudzinski, Old & Gibbs 1993 and regional (Shepherd, Pratt & Taylor 1974) collections of isolates. Some of the studies with P. cinnamomi indicated the existence of host specialisation in pathogenicity (Zentmyer 1980, Zentmyer & Guillemet 1981.…”
Section: Introductionmentioning
confidence: 99%
“…This may also explain, at least in part, the appearance of oospores in certain old cultures of cross-inducing species of Phytophthora (Ashby, 1929;Chee & Newhook, 1965;Kreutzer et a/., 1940;Royle & Hickman, 1964;Savage et al, 1968;Stamps, 1953;Tucker, 193 1) . Brasier (1 972) showed that the ability of aged cultures of certain self-sterile isolates of Phytophthora to form oospores around the inoculum or in sectors in subcultures usually disappeared after one or two transfers.…”
Section: Discussionmentioning
confidence: 98%